Profiling of UGT1A1*6, UGT1A1*60, UGT1A1*93, and UGT1A1*28 Polymorphisms in Indonesian Neonates With Hyperbilirubinemia Using Multiplex PCR Sequencing - Amandito, Radhian; Rohsiswatmo, Rinawati; Carolina, Erica; Maulida, Rizka; Kresnawati, Windhi; Malik, Amarila (Frontiers in Pediatrics, 2019)
Background: Single nucleotide polymorphism (SNP) variants of the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene have been studied as an important factor in neonatal hyperbilirubinemia (jaundice) severity. Specific ethnicities, including Asians, have certain SNPs that appear more frequently than others. Aim: To identify the most common SNPs in Indonesian neonates and their association with the severity of neonatal hyperbilirubinemia. Methods: Eighty-eight inborn and outborn jaundiced infants from three different hospitals (Bengkulu, Jakarta, Biak Papua) across Indonesia were enrolled in this cross-sectional study and their peak total serum bilirubin levels assessed. SNP variant analyses of the TATAA box, promoter, and exon 1 regions of UGT1A1 gene from 78 of the 88 infants were carried out using the SNaPshotR Multiplex Polymerase Chain Reaction (PCR) System followed by DNA sequencing. Results: We detected SNP variants UGT1A1*28, UGT1A1*60, UGT1A1*93, and UGT1A1*6 in our population. Mean total serum bilirubin was 14.59±5.57 mg/dL. Bivariate analyses using delivery location, gestational age, birth weight, mother’s age, and ethnicity were shown to be associated with moderate-to-severe hyperbilirubinemia (p < 0.05). None of the four SNPs appeared to be associated with moderate-to-severe hyperbilirubinemia. In multivariate analysis, however, only the “other ethnic group” (e.g. Chinese, Bengkulu, Papua, Bima) category showed an association with moderate-to-severe hyperbilirubinemia, with an odds ratio of 6.49 (95% CI 1.01-41.67; p < 0.05). Conclusions: We found that the UGT1A1*60 is the most common SNP detected in neonates with hyperbilirubinemia in the Indonesian population. Interestingly, in Indonesia, UGT1A1 polymorphisms do not appear to be associated with differences in the severity of hyperbilirubinemia.